Menjadi ibu hebat untuk menurunkan penolakan ibu terhadap anak dengan gangguan spektrum autis (GSA) - Devia Purwaningrum; Hepi Wahyuningsih; Sumedi P Nugraha (Jurnal Ilmiah Psikologi Terapan, 2018)
Mother acceptance is an important factor in caring for children with autism. A mother that has a high acceptance is capable of developing a positive parenting skill and as a result the children are able to grow optimally. This research aimed to examine the psychoeducation to be a great mother to reduce the rejection towards children with autism. The participants were three mothers who have children with autism. Data collection used the parental acceptance-rejection scale (PARQ). The study design using the experimental quasi of one-group pretest-posttest. Data analysis was conducted through the Friedman Test. The result of statistical test with Friedman Test showed no significant difference between before and after the treatment, q = 1,000, and significance value 0,607 (p> 0.05).